Deintensification or No Statin Treatment Is Associated With Higher Mortality in Patients With Ischemic Stroke or Transient Ischemic Attack. Issue 8 (21st May 2021) - Dearborn-Tomazos, Jennifer L.; Hu, Xin; Bravata, Dawn M.; Phadke, Manali A.; Baye, Fitsum M.; Myers, Laura J.; Concato, John; Zillich, Alan J.; Reeves, Mathew J.; Sico, Jason J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Practice guidelines recommend that most patients receive moderate- or high-potency statins after ischemic stroke or transient ischemic attack (TIA) of atherosclerotic origin. We tested the association of different patterns of potency for prescribed statin therapy—assessed before admission and at hospital discharge for ischemic stroke or TIA—on mortality in a large, nationwide sample of US Veterans. Methods: The study population included patients with an ischemic stroke or TIA occurring during 2011 at any of the 134 Veterans Health Administration facilities. We used electronic outpatient pharmacy files to identify statin dose at hospital admission and within 7 days after hospital discharge. We categorized statin dosing as low, moderate, or high potency; moderate or high potency was considered at goal. We created 6 mutually exclusive groups to reflect patterns of statin potency from hospital admission to discharge: goal to goal, low to goal, goal to low or goal to none (deintensification), none to none, none to low, and low to low. We used logistic regression to compare 30-day and 1-year mortality across statin potency groups. Results: The population included 9380 predominately White (71.1%) men (96.3%) who were hospitalized for stroke or TIA. In this sample, 34.1% of patients (n=3194) were discharged off a statin medication. Deintensification occurred in 14.0% of patients (n=1312) and none to none in 20.5% (n=1924). Deintensification and none to none were associated with a higher odds of mortality as compared with goal to goal (adjusted odds ratio 1-year mortality: deintensification versus goal to goal, 1.26 [95% CI, 1.02–1.57]; none to none versus goal to goal, 1.59 [95% CI, 1.30–1.93]). Adjustments for differences in baseline characteristics using propensity weighted scores demonstrated similar results. Conclusions: Underutilization of statins, including no treatment or underdosing after stroke (deintensification), was observed in approximately one-third of veterans with ischemic stroke or TIA and was associated with higher mortality when compared with patients who were at goal for statin prescription dosing.